Photoelectrochemical and Raman characterization of In2O3 mesoporous films sensitized by CdS nanoparticles - Malashchonak, Mikalai V.; Poznyak, Sergey K.; Streltsov, Eugene A.; Kulak, Anatoly I.; Korolik, Olga V.; Mazanik, Alexander V. (Beilstein Journal of Nanotechnology, 2013)
The method of successive ion layer adsorption and reaction was applied for the deposition of CdS nanoparticles onto a mesoporous In2O3 substrate. The filling of the nanopores in In2O3 films with CdS particles mainly occurs during the first 30 cycles of the SILAR deposition. The surface modification of In2O3 with CdS nanoparticles leads to the spectral sensitization of photoelectrochemical processes that manifests itself in a red shift of the long-wavelength edge in the photocurrent spectrum by 100–150 nm. Quantum-confinement effects lead to an increase of the bandgap from 2.49 to 2.68 eV when decreasing the number of SILAR cycles from 30 to 10. The spectral shift and the widening of the Raman line belonging to CdS evidences the lattice stress on the CdS/In2O3 interfaces and confirms the formation of a close contact between the nanoparticles.
Keywords: cadmium sulfide (CdS); indium oxide (In2O3); nanoparticles; successive ionic layer adsorption and reaction (SILAR)

(untitled) - Grätzel, M. (Nature, 2001)

(untitled) - Vogel, R.; Hoyer, P.; Weller, H. (J. Phys. Chem., 1994)

(untitled) - Rühle, S.; Shalom, M.; Zaban, A. (ChemPhysChem, 2010)

(untitled) - Kamat, P. V. (J. Phys. Chem. C, 2008)

(untitled) - Katoh, R.; Furube, A.; Yoshihara, T.; Hara, K.; Fujihashi, G.; Takano, S.; Murata, S.; Arakawa, H.; Tachiya, M. (J. Phys. Chem. B, 2004)

(untitled) - Nicolau, Y. F. (Appl. Surf. Sci., 1985)

(untitled) - Pathan, H.; Lokhande, C. (Bull. Mater. Sci., 2004)

(untitled) - Baker, D. R.; Kamat, P. (Adv. Funct. Mater., 2009)

(untitled) - Ahmed, R.; Will, G.; Bell, J.; Wang, H. (J. Nanopart. Res., 2012)

(untitled) - Cheng, S.; Fu, W.; Yang, H.; Zhang, L.; Ma, J.; Zhao, H.; Sun, M.; Yang, L. (J. Phys. Chem. C, 2012)

(untitled) - Rabinovich, E.; Hodes, G. (J. Phys. Chem. C, 2013)

(untitled) - Mori, S.; Asano, A. (J. Phys. Chem. C, 2010)

(untitled) - Poznyak, S. K.; Kulak, A. I. (Electrochim. Acta, 2000)

(untitled) - Roy, A.; Sood, A. K. (Phys. Rev. B, 1996)

(untitled) - White, W. B.; Keramidas, V. G. (Spectrochim. Acta, Part A, 1972)

(untitled) - Korotcenkov, G.; Brinzari, V.; Ivanov, M.; Cerneavschi, A.; Rodriguez, J.; Cirera, A.; Cornet, A.; Morante, J. (Thin Solid Films, 2005)

(untitled) - Richter, H.; Wang, Z. P.; Ley, L. (Solid State Commun., 1981)

(untitled) - Roca, E.; Trallero-Giner, C.; Cardona, M. (Phys. Rev. B, 1994)

(untitled) - Trallero-Giner, C.; Debernardi, A.; Cardona, M.; Menéndez-Proupín, E.; Ekimov, A. I. (Phys. Rev. B, 1998)

(untitled) - Nien, Y.-T.; Zaman, B.; Ouyang, J.; Chen, I.-G.; Hwang, C.-S.; Yu, K. (Mater. Lett., 2008)

(untitled) - Romčević, N.; Kostić, R.; Romčević, M.; Čomor, M. I.; Nedeljković, J. M. (J. Phys. D: Appl. Phys., 2005)

(untitled) - Kostić, R.; Romčević, N. (Phys. Status Solidi C, 2004)

(untitled) - Scamarcio, G.; Lugará, M.; Manno, D. (Phys. Rev. B, 1992)

(untitled) - Hwang, Y.-N.; Shin, S.; Park, H. L.; Park, S.-H.; Kim, U.; Jeong, H. S.; Shin, E.-J.; Kim, D. (Phys. Rev. B, 1996)

(untitled) - Brus, L. (J. Phys. Chem., 1986)